Studi Harga Saham Pasca IPO di Bursa Efek Indonesia - Nima, Rosella Virginia Risang (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study provides empirical evidence that the initial share price tends to be lower than the share price over the periods of 1 d and 6, 12, 18, and 24 months thereafter. Methodology: This quantitative research used comparative test-type research with secondary data collection. Data were obtained through the Indonesian Stock Exchange (BEI) and processed using SPSS software. Results/findings: The results obtained in this research show that the initial share price has a positive difference between the post-IPO price for the first day, 6th, 12th and 18th month. However, things are different in the 24th month, when there is no evidence of any price changes occurring. Limitations: IPOs were conducted on the Indonesian Stock Exchange within a specific timeframe (2018-2019), which may limit the generalizability of the findings to other markets or periods. With a total sample that can be taken of 95 issuers with IPO and post-IPO prices can be taken over a period of two years. Contribution: To understand IPO underpricing dynamics. By highlighting the role of underwriters and company signals in shaping investor interest and share price performance, the study offers insights that can inform financial market participants, policymakers and researchers.